History of Statistics in Brazil: Annotated Bibliography - Pereira, Basilio de Bragança (Brazilian Journal of Biometrics, 2025)
In this note, documents related to the history of development of Statistical Science in Brazil are listed and briefly commented. These documents deal with interviews, personal reports, teaching developments and obituaries.